2007
DOI: 10.1103/physrevd.76.047702
|View full text |Cite
|
Sign up to set email alerts
|

Doubly special relativity and Finsler geometry

Abstract: We discuss the recent proposal of implementing Doubly Special Relativity in configuration space by means of Finsler geometry. Although this formalism leads to a consistent description of the dynamics of a particle, it does not seem to give a complete description of the physics. In particular, the Finsler line element is not invariant under the deformed Lorentz transformations of Doubly Special Relativity. We study in detail some simple applications of the formalism. ‡

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 16 publications
0
49
0
Order By: Relevance
“…[30,21,22,37,29], we concluded that classical and quantum gravity models on (co) tangent bundles positively result in generalized Finsler like theories with violation of local Lorentz symmetry. The conclusion was supported also by a series of works on definition of spinors and field interactions on (in general, higher order) locally anisotropic spacetimes [38,39], on low energy limits of (super) string theory [40,41,42] and possible Finsler like phenomenological implications and symmetry restriction of quantum gravity [43,44,45]. Here, we emphasize that the nonholonomic quantum deformation formalism can be re-defined for nonholonomic (pseudo) Riemannian, or Riemann-Cartan, manifolds with fibred structure.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…[30,21,22,37,29], we concluded that classical and quantum gravity models on (co) tangent bundles positively result in generalized Finsler like theories with violation of local Lorentz symmetry. The conclusion was supported also by a series of works on definition of spinors and field interactions on (in general, higher order) locally anisotropic spacetimes [38,39], on low energy limits of (super) string theory [40,41,42] and possible Finsler like phenomenological implications and symmetry restriction of quantum gravity [43,44,45]. Here, we emphasize that the nonholonomic quantum deformation formalism can be re-defined for nonholonomic (pseudo) Riemannian, or Riemann-Cartan, manifolds with fibred structure.…”
Section: Introductionmentioning
confidence: 81%
“…The solutions for the "cotangent" gravity are, in general, with violation of Lorentz symmetry induced by quantum corrections. The nature of such quantum gravity corrections is different from those defined by FinslerLagrange models on tangent bundle (see, for instance, [33,34,43,44,45])), locally anisotropic string gravity [40,41,42] with corrections from extradimensions and nonholonomic spinor gravity [37,38,39] and noncommutative gravity, see reviews of results in [29,30]. The aim of this section is to analyze how a generalization of Einstein gravity can be performed on cotangent bundles in terms of canonical * φ-connections, with geometric structures induced by an effective Hamiltonian fundamental function, when the Fedosov quantization can be naturally performed.…”
Section: Quantum Gravitational Field Equationsmentioning
confidence: 99%
“…However (29) is a single equation (as opposed to (39) which is a system of PDEs). For one's purposes, to control the two unknown functions a and b, one needs to adopt (39) as the Finslerian generalization of the gravitational field equations. The weak field approximation was also investigated by X. Li and Z. Chang [33], yet starting from Finslerian field equations (for space containing matter) based on the horizontal curvature tensor R α λνμ (as proposed in [32]) rather than K α λνμ .…”
Section: Linearized Field Equationsmentioning
confidence: 99%
“…We refer to (39) as Rutz's field equations (for the free space). Note that (39) is a nonlinear system of partial differential equations, so that a field g λμ governed by (39) will serve as part of its own source. The feedback effect of the Finslerian gravitational field may be neglected only when the field is weak, e.g.…”
Section: Linearized Field Equationsmentioning
confidence: 99%
See 1 more Smart Citation